(untitled) (Quinto Sol, 2021)
The article analyzes the book The President, by Julio Costa (governor of the province of Buenos Aires in the 1890s), published simultaneously with the electoral reform of 1912. It is argued that the relevance of this text lies in three axes. First, it shows key topics of the public debate of that moment: representative government, political parties, secret and mandatory voting. Second, it ponders universal suffrage in the name of preserving traditions and the defense of freedom. Thus, it offers indications of possible crossings between conservatism, liberalism and democracy in Argentina of 1910s. Finally, the book displays a severe criticism of Roque Sáenz Peña inspired by The Prince, the famous text by Nicolò Machiavelli. From this point of view, it integrates a broader sequence, so far little explored: a political reflection grounded in the Florentine author about the vicissitudes of Argentine public life of the first decades of the twentieth century.